2020
DOI: 10.24018/ejdent.2020.1.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A Bizarre Presentation of Bilateral Mandibular Osteoporotic Bone Marrow Defect (A Case Report)

Abstract: BACKGROUND: Osteoporotic bone marrow defect of the jaw is an uncommon localized radiolucency that consists of hematopoietic red marrow with varying amounts of fatty yellow marrow. The lesion is usually asymptomatic and accidentally discovered during a routine radiographic examination; however, some studies showed different results. CASE REPORT: This is an uncommon case of bilateral mandibular osteoporotic bone marrow defect in a 40-year- old healthy female. One of the defects reoccurred, and it involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Patients were all asymptomatic in 13 articles, but some studies documented symptoms ( Crawford and Weathers, 1970 , Sanner and Ramin, 1977 , Schneider et al, 1988 , Correll and Wescott, 1983 , Sa’do et al, 1992 , Bouquot et al, 2002 , Sençimen et al, 2011 , Almeida et al, 2014 , Garcia et al, 2015 , Yesancas-Pallares et al, 2016 , Kim et al, 2017 , Al-Ramzi et al, 2020 ;). Pain and edema were among the reported symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients were all asymptomatic in 13 articles, but some studies documented symptoms ( Crawford and Weathers, 1970 , Sanner and Ramin, 1977 , Schneider et al, 1988 , Correll and Wescott, 1983 , Sa’do et al, 1992 , Bouquot et al, 2002 , Sençimen et al, 2011 , Almeida et al, 2014 , Garcia et al, 2015 , Yesancas-Pallares et al, 2016 , Kim et al, 2017 , Al-Ramzi et al, 2020 ;). Pain and edema were among the reported symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…All cases performed biopsies to confirm the diagnosis, and two studies made a curettage in the lesion ( Haen et al, 2009 , Al-Ramzi et al, 2020 ). Only one study reported a lesion follow-up after the biopsy ( Almeida et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations